Seismic structure of the upper crust from 0-75 Ma in the equatorial Atlantic Ocean on the African plate using ultralong offset seismic data - Audhkhasi, P. (2021)
The uppermost oceanic crust composes of Layers 2A and 2B, and the boundary between them is debated to be a lava/dike transition or a hydrothermal alteration boundary within the lava unit. Here, we present the analyses of ultralong multichannel seismic data along a 1,500 km long profile covering 0–75 Ma of the oceanic lithosphere on the African plate in the equatorial Atlantic Ocean. We find that the Layer 2A is observed along the whole profile, with its urn:x-wiley:ggge:media:ggge22094:ggge22094-math-0001 velocity increasing from 2.5 km/s near the ridge axis to urn:x-wiley:ggge:media:ggge22094:ggge22094-math-00024 km/s at urn:x-wiley:ggge:media:ggge22094:ggge22094-math-00034 Ma with slight variations thereafter. We also find that the sediment thickness increases rapidly from 0 m at the ridge axis to 170 m at 4 Ma, suggesting that there is a link between the high sedimentation rate and the increase in Layer 2A velocity. These observations indicate that crust younger than 4 Myr may be influenced by active hydrothermal circulation. The observed thickness of Layer 2A decreases from urn:x-wiley:ggge:media:ggge22094:ggge22094-math-0004850 m near the ridge axis to urn:x-wiley:ggge:media:ggge22094:ggge22094-math-0005600 m at 15 Ma with no significant changes beyond. We also find an increase in Layer 2B velocity from 5.1 km/s at 4 Myr to 5.5 km/s at 46 Myr, suggesting that passive hydrothermal circulation may extend deeper than Layer 2A/2B boundary. We propose Layer 2A/2B boundary to be a lava/dike transition at the ridge axis and a hydrothermal alteration boundary within the extrusive section away from the ridge axis.